Comparative Analysis Research of Safety Climate Assessment in the Jababeka Manufacturing Industry - Satrya, Chandra; Susilowati, Indri Hapsari; Khaliwa, Agra Mohamad; Alam, Eriena Nur (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: The manufacturing industry transforms various materials, substances, or components into new products using mechanical, physical, or chemical forces. Safety climate refers to the perception of workers of prioritizing safety over organizational goals in the workplace. PT A, B, and C are manufacturing companies located in the Jababeka area. This study aims to identify the main factors that influence the perception of workers of safety climate in PT A, B, and C. Methods: A quantitative study with a cross-sectional design was conducted in August 2021 to analyze the safety climate of three companies. This study focused on various factors, such as leadership, risk management, implementation of occupational health and safety management system (OHSMS), regulation, management commitment, worker engagement, and worker competence. The sample size consisted of 330 workers selected from the three companies using the Lemeshow formula from a total of 1500 workers using the cluster sampling technique with the analysis of variance (ANOVA) test. Results: The results showed that risk management had the lowest score among the safety climate sub-variable for the three companies. Conclusion: The ANOVA test revealed a significant relationship among the safety climate variables. Furthermore, it is necessary to prioritize management in terms of policy and administration by involving all departments.